Labor and Services as Information Carriers in Emergy-LCA Accounting - Ulgiati, Sergio; Brown, Mark T. (Journal of Environmental Accounting and Management, 2026)
Production and consumption processes in national and local economies are supported by free renewable environmental resources as well as by nonrenewable minerals and fuels. Economies measure the values of these resources in money terms. It is not always clear that money does not pay nature for providing resources, but only pays humans for extracting, processing and delivering them within markets. Emergy Accounting (EMA) is an environmental accounting method based on the recognition of the work done by nature in generating mineral and energy resources. The work of nature is accounted for in terms of solar equivalent energy supporting natural capital formation and the supply of ecosystem services. Human labor and services are also supported by solar emergy flows and contribute energy and information to economic processes. This paper discusses the role of labor in production processes and designs appropriate accounting schemes based on the emergy approach. The Life Cycle Assessment method (LCA) as well as other resource assessment schemes do not include labor and services in their accounting framework. By keeping track of environmental resources supporting labor and services, emergy provides an important and much needed contribution to a more comprehensive assessment of economic and societal dynamics.